Performance and Low Power Driven Floorplanning - Ning Xu; Zhoughua Jiang; Feng Huang (Journal of Algorithms & Computational Technology, 2007)
In this paper, a floorplanning methodology aimed at low power design is presented. The fuzzy technique and the simulated annealing algorithm are employed aiming at low power dissipation and high performance. Due to the imprecise nature of design information at the floorplanning stage, the various objectives are expressed in a fuzzy domain. The search is made on a vector of fuzzy goals. The performance of the proposed algorithm is evaluated using selected MCNC benchmark circuits. The results obtained using the proposed algorithm are compared to those obtained using other methods.